Peran Etika Profesi Pendidik Dalam Mewujudkan Karakter Peserta Didik Yang Baik - Ahmad Rinaldi Siregar; M. Muflih Dermawan; Lucky Tirta Nurrarfiansyah; Fachri Habib; Agung Muhammad Nur; Syafri Fadhilah Marpaung (Jurnal Pendidikan Sosial Dan Konseling, 2023)
This research was conducted to deepen the role of professional ethics in educators. This type of research uses the literature study research method. Zed in Kartiningsih’s research (2015) said that the literature study method is a series of activities relating to methods of collecting library data, reading and taking notes, and managing materials. Study. Professional ethics is an attitude of life to meet the professional service needs of clients with involvement and expertise as a service within the framework of the obligations of society as a whole towards members of society who need it accompanied by careful reflection. To become a professional teacher is not easy, you must have special requirements and you must know the ins and outs of educational theory.